Central de serviços compartilhados numa corporação multinacional de manufatura: um estudo de caso em confecção de moldes usinados - Klein, Rodrigo César (Universidade do Vale do Rio dos Sinos, 2024)
Considering a competitive scenario, the efficient usage of resources in a global network is an important challenge for companies with strategic business units in different places. Many companies have implemented shared services centers to increase the efficiency of their support activities such as Information Technology, Human Resources or Controlling and Financial. Studies show that companies that migrate to this shared service centers approach reduce costs up to 30% in such areas, when compared to the regular structure where supporting services are not centralized. In this context this paper aims to analyze an international manufacturer company and identify the critical success factors to implement a shared service center. The working method is a case study with qualitative approach. The results presented in this paper show the critical success factors and the challenges involved in the implementation of a shared service center (shown in a theoretical model), as much as the steps to make it operational in the company studied. Additionally, the case present in the initial stage approximately 1,5 million reais (~300 tousand USD by exchange rate from August 2024) in sales volume and 700 tousand reais (~130 tousand USD by exchange rate from August 2024) in fixed cost absorption.
Keywords: Central de Serviços Compartilhada (CSC); Áreas de suporte ou apoio; Unidades de negócio; Redução de custo; Aumento de eficiência; Shared service centers (SSC); Support tasks; Strategyc Business Units (SBUs); Cost reduction; Efficiency increasing; ACCNPQ::Engenharias::Engenharia de Produção